2023
DOI: 10.1002/cncr.34766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupuncture versus usual care on sleep quality in cancer survivors with chronic pain: Secondary analysis of a randomized clinical trial

Abstract: Background Chronic pain negatively affects sleep; it is unclear whether pain relief from acupuncture contributes to sleep quality improvements in cancer survivors. This study aimed to evaluate the effect of acupuncture versus usual care on sleep quality among cancer survivors with comorbid sleep disturbance and chronic musculoskeletal pain. Methods Sleep outcome data from the Personalized Electroacupuncture Versus Auricular Acupuncture Comparative Effectiveness (PEACE) randomized clinical trial were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…They discovered that electroacupuncture and auricular acupuncture caused a clinically meaningful and long-lasting enhancement of sleep quality in cancer survivors with concomitant sleep disruption and chronic pain. Acupuncture, according to their findings, may be an evidence-based nonpharmacologic strategy for improving sleep health in cancer survivors who are in pain [ 83 ]. The preliminary findings from a remarkable trial by Reddy et al indicated that cancer patients might effectively transition from opioids to levorphanol utilizing an opioid rotation ratio (ORR) of 8.5.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that electroacupuncture and auricular acupuncture caused a clinically meaningful and long-lasting enhancement of sleep quality in cancer survivors with concomitant sleep disruption and chronic pain. Acupuncture, according to their findings, may be an evidence-based nonpharmacologic strategy for improving sleep health in cancer survivors who are in pain [ 83 ]. The preliminary findings from a remarkable trial by Reddy et al indicated that cancer patients might effectively transition from opioids to levorphanol utilizing an opioid rotation ratio (ORR) of 8.5.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have shown that AC can rapidly reduce pain in cancer survivors with pain and insomnia, which can contribute to the reduction of insomnia. 85,191 However, these studies generally suffer from the disadvantage of small sample sizes.…”
Section: Improving Quality Of Life and Emotional Well-beingmentioning
confidence: 99%
“…However, other studies have demonstrated that AC can provide clinically significant and long‐lasting benefits for cancer survivors 83,84 and patients 81,85 with CRI. Furthermore, some studies have shown that AC can rapidly reduce pain in cancer survivors with pain and insomnia, which can contribute to the reduction of insomnia 85,191 . However, these studies generally suffer from the disadvantage of small sample sizes.…”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%
“…[8][9][10][11] There is a growing body of evidence showing that the use of acupuncture has positive implications for improving cancer-related symptoms and enhancing the quality of life of cancer patients. [12,13] Although this state of affairs is gradually gaining attention among scholars, there has not been a systematic review to organize and summarize the research in this area in detail. Therefore, this study summarizes and combs the research in this field through bibliometric analysis methods to explore the current research hotspots and future research trends.…”
Section: Introductionmentioning
confidence: 99%